2018
DOI: 10.5032/jae.2018.04301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Mechanics Camp on Intentions To Teach

Abstract: Targeted teacher recruitment is suggested as a way to alleviate the teacher shortage in specific content areas such as agricultural mechanics. Learning experiences are linked to increased selfefficacy and increased interest in specific career pursuits. The Agricultural Mechanics Power & Design (AMP'D) Experience was developed as a learning experience to enhance high school student skills in agricultural mechanics and expose them to the career of teaching agricultural mechanics at the high school level. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For instance, Byrd et al (2015) reported a statistically significant and positive relationship between the number of post-secondary credit hours completed in agricultural mechanics and SBAE teachers' perceived level of competence in the subject area. Regarding experience, previous research has also shown that experiential learning activities in agricultural mechanics influenced high school students' intentions to teach secondary agricultural education (Gorter & Swan, 2018). Statistically significant and positive relationships have also been demonstrated among students' agricultural mechanics experience at the secondary level, intention to enroll in agricultural mechanics coursework at the post-secondary level, and perceived importance of teaching agricultural mechanics skills (Rasty et al, 2017;Wells et al, 2013).…”
Section: Introduction and Review Of Literaturementioning
confidence: 87%
“…For instance, Byrd et al (2015) reported a statistically significant and positive relationship between the number of post-secondary credit hours completed in agricultural mechanics and SBAE teachers' perceived level of competence in the subject area. Regarding experience, previous research has also shown that experiential learning activities in agricultural mechanics influenced high school students' intentions to teach secondary agricultural education (Gorter & Swan, 2018). Statistically significant and positive relationships have also been demonstrated among students' agricultural mechanics experience at the secondary level, intention to enroll in agricultural mechanics coursework at the post-secondary level, and perceived importance of teaching agricultural mechanics skills (Rasty et al, 2017;Wells et al, 2013).…”
Section: Introduction and Review Of Literaturementioning
confidence: 87%